Nilai-Nilai Pendidikan Islam Moderat dalam Acara Tradisi Ruwah Desa: Studi Etnografi di Dusun Plosokuning Penompo Mojokerto - Zamzami, Abdul Mufid; Nur Aziz, Imam (Kopertais Wilayah I DKI Jakarta dan Banten, 2025)
This study examines the Ruwah Desa tradition in Dusun Plosokuning, Mojokerto, within the framework of moderate Islamic educational values. This tradition represents a form of cultural and religious acculturation passed down through generations, embodying the values of togetherness, tolerance, and respect for ancestors. Employing a qualitative approach with ethnographic methods, this study explores the implementation, meaning, and adaptation of Ruwah Desa in the daily lives of the local community. Data were collected through participatory observation, in-depth interviews with community leaders, and documentation of various processions within the tradition. The findings indicate that the Ruwah Desa tradition serves as a medium for strengthening social solidarity, maintaining harmony between culture and Islamic teachings, and educating the younger generation on moderate Islamic values. This tradition encompasses four fundamental principles of moderate Islam: i‘tidal (justice), tasamuh (tolerance), tawazun (balance), and tawassuth (moderation), which are reflected in the practices of mutual cooperation, communal prayers, and the slametan or kenduren ritual. The study confirms that local traditions such as Ruwah Desa play a vital role in fostering religious moderation and reinforcing community cohesion. Beyond enriching the discourse on cultural and religious interactions, this study offers practical insights into the preservation of local traditions in the modern era. Thus, Ruwah Desa is not merely an annual ritual but also a manifestation of an inclusive and adaptive interpretation of Islam in response to contemporary societal developments.